Coparenting Conflict and Cooperation between Parents and Grandparents in Vietnamese Families: The Role of Grandparent Psychological Control and Parent–Grandparent Communication. Issue 3 (25th September 2019) - Hoang, Nam‐Phuong T.; Haslam, Divna; Sanders, Matthew
Abstract : Shared care between parents and grandparents is common in Asian cultures. This cocare practice provides many benefits to families but is also particularly complex, as both parents and grandparents must simultaneously fulfill their roles as cocaregivers as well as maintain their relationship with each other. This study aims to explore the determinants of coparenting relationships between parents and grandparents in Vietnam. Data were collected from 501 Vietnamese parents whose aging parents are active carers for their children. The results indicated that grandparent psychological control and parent–grandparent quality of communication explain the largest variance in both parent–grandparent coparenting conflict and cooperation. The results suggest that parenting interventions aimed at the Asian cultures, where grandparent care is common, may benefit from the inclusion of a content focus on promoting the coparenting relationship between parents and grandparents. Abstract : El cuidado compartido entre abuelos y padres es común en las culturas asiáticas. Esta práctica de cocuidado ofrece muchos beneficios a las familias pero también es particularmente compleja, ya que tanto los padres como los abuelos deben cumplir sus roles simultáneamente como cocuidadores y también mantener su relación mutua. Este estudio tiene como finalidad analizar los determinantes de las relaciones de cocrianza entre los padres y los abuelos en Vietnam. Se recopilaron datos de 501 padres vietnamitas cuyos padres de la tercera edad son cuidadores activos de sus hijos. Los resultados indicaron que el control psiscológico de los abuelos y la calidad de la comunicación entre los padres y los abuelos explican la mayor varianza en el conflicto y la cooperación en la cocrianza entre padres y abuelos. Los resultados sugieren que las intervenciones en la crianza orientadas a las culturas asiáticas, donde el cuidado de los abuelos es común, pueden beneficiarse de la inclusión de un contenido centrado en promover la relación de cocrianza entre padres y abuelos. Abstract : 在亚洲文化里, 祖辈和父母一起抚养孩子是很普遍的现象。这种共同养育的做法给家庭带来很多好处, 特别是极其复杂的大家庭。父母和祖辈必须同时实现共同照料孩子的角色, 和保持同彼此的关系。本研究旨在探究在越南, 共同抚养孩子的父母和祖辈之间的关系的决定因素。数据来自501位越南家长, 他们的老年父母也是孩子的积极看护者。结果表明祖辈的心理控制和父母‐祖辈之间的交流质量解释了在父母‐祖辈共同养育冲突和合作方面的最大的差异。本研究结果表明在祖辈参与照看孩童的亚洲文化里, 对养育方式的干预可以包含那些以促进父母和祖辈之间的共同养育关系为重点的培训内容。